2020
DOI: 10.1177/2050313x20933104
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial injury after administration of intravenous epinephrine for allergic reaction

Abstract: Myocardial injury or infarction in the setting of anaphylaxis can be due to anaphylaxis itself, known as Kounis syndrome, or as a result of treatment with epinephrine. Myocardial ischemia caused by therapeutic doses of epinephrine in the setting of anaphylaxis is a rare event attributed to coronary artery vasospasm. A 41-year-old female with past medical history of recurrent costochondritis, chronic thrombocytopenia, and nonspecific palindromic rheumatism presented to the emergency department with perioral num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Other side effects described included decreased ejection fraction, diagnosis of cardiomyopathy, and coronary artery thrombus that was diagnosed on cardiac catheterization 19–22 . The other case reports described 34 patients in total who received an intravenous bolus dose of epinephrine inadvertently, or an inappropriately high IM dose 23–52 . This led to a wide array of side effects including arrhythmias, cardiomyopathy, thrombus, and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Other side effects described included decreased ejection fraction, diagnosis of cardiomyopathy, and coronary artery thrombus that was diagnosed on cardiac catheterization 19–22 . The other case reports described 34 patients in total who received an intravenous bolus dose of epinephrine inadvertently, or an inappropriately high IM dose 23–52 . This led to a wide array of side effects including arrhythmias, cardiomyopathy, thrombus, and cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…97 Arrhythmia and acute coronary syndrome after intramuscular epinephrine are rare with only 7 case reports described in the literature. 98 Antihistamines, corticosteroids, and mast cell stabilizers such as cromolyn are commonly prescribed in the acute setting because they may mitigate certain symptoms of allergic reactions (eg, pruritus, urticaria, abdominal discomfort), and patients and clinicians express more comfort and familiarity with these medications than with epinephrine. 75 However, unlike epinephrine, these medications do not interrupt acute mast cell degranulation and do not stop anaphylaxis.…”
Section: Emergency Care Plans and Medicationmentioning
confidence: 99%
“…A 2021 meta-analysis of 86 studies, comprising datasets from 20 prospective and 68 retrospective observational studies (36 557 anaphylaxis events), showed that although 1 in 10 anaphylactic events were associated with the need for more than 1 epinephrine dose, only 2.2% (95% CI, 1.1%-4.1%) of reactions were associated with failure to respond to 2 doses of epinephrine . Arrhythmia and acute coronary syndrome after intramuscular epinephrine are rare with only 7 case reports described in the literature . Antihistamines, corticosteroids, and mast cell stabilizers such as cromolyn are commonly prescribed in the acute setting because they may mitigate certain symptoms of allergic reactions (eg, pruritus, urticaria, abdominal discomfort), and patients and clinicians express more comfort and familiarity with these medications than with epinephrine .…”
Section: Treatment Of Patients With Food Allergiesmentioning
confidence: 99%
“…Furthermore, elevated levels of cardiac enzymes, tryptase, and eosinophilia can also serve as indications of Kounis syndrome. In all reported cases involving pediatric patients, ischemic changes (ST elevation and ST depression) were observed on the ECG, except for one case where a 15-year-old patient with Kounis syndrome, due to a wasp sting, displayed normal findings on the ECG [ 34 , 40 , 64 - 66 , 72 , 83 - 90 ]. Similarly, in the case of the adult case reports, it was also observed that ischemic changes were noted on the electrocardiogram (ECG).…”
Section: Reviewmentioning
confidence: 99%